Spatiotemporal Gait Changes During Pregnancy: A Literature Review - Fatmarizka, Tiara; Carissa, Vivian Jennie Diva; Susilo, Taufik Eko (FISIO MU: Physiotherapy Evidences, 2023)
Background: Pregnant women experience several changes that can be seen from a spatiotemporal perspective and the parameters are stride length, stride width, walking speed, walking cadence, cycle time, step time. The importance of knowing changes in gait patterns in pregnant women in order to reduce the risk of falling and improve the quality of life of pregnant women. Purpose: The purposes of the study were to know the measurement or instrument used as a spatiotemporal parameter, the results of the changes and the factors that influence changes in gait patterns in pregnant women from a spatiotemporal point of view. Method: The study using the literature review method by assessing articles with critical appraisal on six articles using JBI's Critical Appraisal. The databases were Google Scholar, National Center for Biotechnology Information (NCBI), PubMed, Science Direct, Garuda Portal, InaBJ with keywords, “pregnancy” OR “pregnant women” OR “pregnant” AND “gait” OR “biomechanics” OR “spatiotemporal”. All articles would be organized, remove duplicate articles using EndNote, appraisal, and quality assessment for the risk of bias. Results: based on the finding the result from databases, there were 6 articles used for assessment and appraisal. Conclusion: increased lumbar lordosis, decreased stride length, decreased walking rhythm, decreased duration of single support, increased duration of double support, increased COP/COG angle were the determinant factors of the spatiotemporal gait changes during pregnancy.